Meningkatkan Kemampuan Membaca, Menulis dan Berbicara dalam Bahasa Indonesia pada Peserta Didik Kelas 1 Sekolah Dasar Melalui Gamifikasi - Ade Eva Novianti (Jurnal Syntax Admiration, 2024)
Indonesian is a unified language where Indonesian is a mother tongue that needs to be owned and instilled from an early age. In every level of education, Indonesian is taught according to the students' developmental stages. However, in practice in the field, many people find a lack of ability to read, write and speak Indonesian, especially in educational institutions that use a foreign language as one of the introductory words in every lesson. The research aims to improve the ability to read, write, and speak Indonesian at the elementary school level. The subjects of this research were 21 grade 1 students at XYZ Private Elementary School in Tangerang. This research explains how gamification can improve students' reading, writing, and speaking skills. The research method used is Classroom Action Research (PTK). The research results show that reading, writing, and speaking skills can be improved through gamification learning methods.